Genome-wide analysis of the Siboney de Cuba cattle breed: genetic characterization and framing with cattle breeds worldwide - Cendron, Filippo; Ledesma-Rodríguez, Anel; Mastrangelo, Salvatore; Sardina, Maria Teresa; Díaz-Herrera, Dervel Felipe; Uffo Reinosa, Odalys; Cassandro, Martino; Penasa, Mauro (Frontiers in Genetics, 2024)
The aim of this study was to perform the first genomic characterization of the Siboney de Cuba breed, a successful hybrid breed resulting from the crossbreeding of Cuban Zebu and Holstein, using SNP array chip. Genetic diversity indices, runs of homozygosity (ROH), and copy number variants (CNV) were identified. Six ROH islands containing a total of 50 genes were discovered, some of which were uncharacterized loci. Furthermore,792 CNV with higher occurrence of genetic material loss were observed. The overall genome coverage for CNV regions was 2.16%. The Siboney de Cuba exhibited a good level of genetic variability with high heterozygosity and low inbreeding when compared with other cattle breeds worldwide. Also, the breed shared genetic similarity to hybrids from America and Bos indicus from Africa and highlighted a moderate level of genetic isolation with some overlaps with Bos taurus from America. The breed showed a complex genetic composition, influenced by historical factors. Overall, findings of the present study contribute to the understanding of genomic structure of Siboney de Cuba cattle breed.